The Role of the Family Hope Program in Providing Social Protection to the Community in Negeri Kamal, West Kairatu District, West Seram Regency - Tomatala, Sevni; Pinoa, Wiclif Sepnath; Riry, Johan (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
The Family Hope Program (PKH) is a social protection program that provides cash assistance to poor households (RTSM) designated as beneficiary families. This research was carried out in Negeri Kamal, West Kairatu District, West Seram Regency, in July 2022 through data collection methods, including observation, interviews, and questionnaires. The research results show that PKH has been in Negeri Kamal since 2015. This Family Hope Program provides relief for people experiencing poverty in helping their economy and helping their children in education, in this case, elementary, middle, and high school. For health for pregnant/postpartum women and toddlers, as well as social welfare for severe disabilities. In addition, assistance in the form of cash and non-cash is conditional for low-income families